Pengaruh Pengembangan Karir dan Keterikatan Kerja Terhadap Kinerja Pegawai dengan Kepuasan Kerja sebagai Variabel Mediator di KPP Pratama Pare - Santosa, Eddy; Rahmawati, Zulfia (Otonomi, 2024)
Employees are one factor which is very important for the organization to achieve target. Increasing employee performance is influenced by several factors including career development, work engagement, and job satisfaction. The purpose of this research is to determine the influence of career development and work engagement partially on job satisfaction, and job satisfaction partially on performance, the influence of career development on performance with job satisfaction as a mediating variable, and the influence of work engagement on performance with job satisfaction as a mediating variable at KPP Pratama Pare. The method in this research is a quantitative method. The population in this study was KPP Pratama Pare employees, totaling 101 people, where the entire population was used as the research sample. This research data collection technique uses questionnaire distribution and personnel documentation data. This research uses the path analysis method. The results of this research data analysis show that KPP Pratama Pare employees: 1). Career development influences job satisfaction, 2). Work engagement influences job satisfaction, 3). Career development influences performance, 4). Work engagement influences performance, 5.) Job satisfaction influences performance, 6). Career development influences performance with job satisfaction as a mediating variable, 7). Work engagement influences performance with job satisfaction as a mediating variable.